(3TQM LOGhd RjL RchWhs - (3CMeO Hf HdbGSe Hf bGSe GdMLOQi GdCfOdSjs; (3RchWh (B( (3RchW (B) (3GdYHQGfjs
(3ChdgG (B:s
(3GdHGH GdChd ai eYQaI GdWGdY (B: (3GdMeO ddg ceG jfHZi dceGdg JShjI GdHjhJ GYde Cf Chd eG JYQa Cf ai GHJOGA GdLOGhd GKfi YTQ LOhdkG s
(3BNQgG (B:s
(3hYOd GdbeQ dPdc Gdjhe hGdSGYI hOQLJg ajgG gi GdOQLI GdeMbbg eTQbI Ch eZQHI dSGYI GdhdGOI GfJgJ GdQSGdI ddLOGhd GdeJQLeI ef YHQGfi Edi dZI GddGJjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs